The Contribution of the Geographic Information System GIS in the Definition of Water Potential Zones in the Abou Ali Watershed (North Lebanon) - Douha Akkari (Revue de Géographie Alpine)
Lebanon is a Mediterranean country with an area of 10,452 km2 65% of this area is karst, therefore Lebanon is rich in surface and underground water but despite these conditions which ensures to meet the need for water, Lebanon has a water shortage due to a few reasons such as: poor management of water resources, Mediterranean climate with interannual variability (6 months of drought). This water situation necessitates a specific study for the purpose of finding an effective solution to the problem of water scarcity. The objective of this work is to determine the areas favorable to the recharge of the Abu Ali watershed (North Lebanon) based on a cartographic approach, thus using the geographic information system (GIS). The detection of these potential zones of groundwater recharge requires a crossing of the relative spatial information of the various parameters (lithology, soil, lineament density, drainage density, slope and land use) influencing the recharge and mapped in this article. A reclassification followed by a weighting of these parameters was performed according to their degree of influence in the recharging process and following an analysis of the CSI cumulative score index. These analyzed parameters are then integrated into a GIS in order to establish a map of potential groundwater recharge areas. The application of the water potentiality model shows that 13% of the area of the basin has a very high-water potentiality especially in the South-East, 39% shows an average potentiality in areas with marly-sandy and limestone-marly lithology, and 20% denote a low potential, especially in the west and in the center of the basin.